An evidence based review on effect of oral motor therapy on feeding in preterm infants - Jani, Priyaben; Verma, Neha (International Journal of Research in Medical Sciences, 2023)
Present study was done to know the effect of Oral Motor Therapy on preterm infants for feeding and related issues. Most preterm infants have low body weight, immature brain development, sucking and swallowing problems, and decreased oral motor ability, which affects infants' growth and normal development. Oral Motor Therapies are used to increase functional strength and control of movement for feeding, to promote the onset of oral feeding, and to improve oral feeding performance. The study started with the search articles on Google Scholar, ResearchGate, Cochrane and PubMed with keywords in range of year 2012-2023. 250 articles were found from the sources. 46 articles were studied which were related to aim of the study. From all of them 10 articles were selected on the basis of inclusion criteria. All the articles suggested improvement in all the post intervention outcomes which showed clinical significance of the Oral Motor Therapy. The study hereby concluded that Oral Motor Therapy is useful in preterm infants for feeding initiation and progression, weight gain as well as in dysphagia rehabilitation and reduced hospital stay.